The factors that influence impulse buying behavior: An empirical study of Muslim credit card holders in Malaysia / Siti Hajar Salwa Ahmad Musadik - Siti Hajar Salwa , Ahmad Musadik (2018)
The impulse buying research was substantially conducted in developing countries by the previous researcher. However, this impulse buying behavior study was rarely conducted in Asian countries, especially in Malaysia. The empirical study of impulse buying in Malaysia is limited. Besides, a study of the variables of materialism, sale promotion, money and time availability, hedonic motivation, self-hisbah, credit card usage, and religiosity also rather sparsely have been done in impulse buying behavior study. In Malaysia, impulse buying behavior had been reported as one of the main factors contribute towards debt woes. Therefore, this study would like to examine the relationship of situational variable (sale promotion, money and time availability) and individual variable (materialism, hedonic motivation, and self-hisbah) as well as the function of credit card usage as mediation variable and religiosity as moderator variable with impulse buying behavior among Muslim credit card holders in Malaysia. This research framework was developed and tested based on the Theory of Buyer Behavior, Theory of Maqasid Shariah, and Engel, Blackwell, and Miniard Model (EBM Model). In terms of instrument development, this study instrument consisted of 81 items adopted and adapted from previous studies. Questionnaires were distributed to 1,000 Muslim credit card holders in Malaysia via purposive and snowball sampling and only 710 questionnaires were returned safely and only 635 usable questionnaires for final data analysis. The analysis was performed via Partial Least Square (PLS-SEM) analysis. The result found that materialism, sale promotion, money and time availability, and hedonic motivation have a significant positive relationship on impulse buying behavior, whilst self-hisbah has a significant negativee relationship with impulse buying behavior. This result also found credit card usage mediates the relationship between materialism, sale promotion, and hedonic motivation on impulse buying behavior but does not mediate the relationship between money and time availability on impulse buying behaviour. In addition, the result also shows the variable of religiosity does not moderate the relationship between materialism and hedonic motivation and impulse buying behaviour. In conclusion, the Theory of Buyer Behavior, Theory of Maqasid Shariah, and Engel, Blackwell, and Miniard Model (EBM Model) are an appropriate basic theory of this study as it can clarify the relationship between the variables.